Mediating Mechanism to Loyalty: Evidence from Indonesia’s Halal Coffee Shop Sector in a Sustainability-Oriented Framework - Rimadini, Amalia; Sudarijati; Silaningsih, Endang (Institut Agama Islam Negeri Parepare, 2025)
Purpose – This study investigates how service quality and promotion influence customer loyalty through the mediating role of customer satisfaction in the rapidly expanding halal coffee shop sector in Indonesia. Recent shifts in consumer behavior toward value-driven, ethical, and sustainability-oriented consumption have repositioned loyalty as a strategic indicator of long-term business resilience in Muslim-majority markets. Drawing on SERVQUAL, Expectation–Confirmation Theory, and principles of Shariah service ethics, this research employs a quantitative approach using 100 valid responses collected through non-probability and accidental sampling. Method – Data were analyzed using descriptive statistics, path analysis, and Sobel testing to assess the significance of the mediating effects. Findings – The findings show that service quality and promotion positively and significantly affect customer satisfaction and loyalty, while satisfaction itself serves as a strong mediating mechanism that strengthens the indirect effects of both predictors.. Pratical Implication – This study contributes theoretically by integrating Islamic ethical perspectives into mainstream loyalty models, and practically by offering sustainability-driven implications for halal-based service enterprises. Originality/value – These results highlight the strategic importance of delivering trustworthy, ethical, and sustainable service experiences aligned with Shariah values to cultivate long-term customer attachment